The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41597-023-02019-z
|View full text |Cite
|
Sign up to set email alerts
|

The shape parameters of coal and gangue particles derived from 3D scanning

Abstract: The irregular shape of mineral particles directly affects the angle of repose, bulk density and flow-properties, and the interaction behaviour between the particles and a contact surface. This paper presents a dataset of spatial data and shape parameters collected from 37 gangue particles and 135 anthracite coal particles, which come from the Shangzhuang Coal Mine. The particle surface models were obtained by a Wiiboox white light raster 3D scanner and Reeyee software. To obtain the scanning surface, each part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Yet, scholars like Liu et al 38 found that the particle size of the broken coal by the drum trunnion obeys a certain distribution and exhibits fractal characteristics through experimental research. Also, Yang et al 39 constructed 3D cloud maps of 135 typical coal particles with a 3D laser scanner, and provided a corresponding database. Therefore, combining the existing data and literature results 7 , the four-sphere filling model is selected for modeling the simulated particle shape in this paper, as shown in Fig.…”
Section: Simulation Modelingmentioning
confidence: 99%
“…Yet, scholars like Liu et al 38 found that the particle size of the broken coal by the drum trunnion obeys a certain distribution and exhibits fractal characteristics through experimental research. Also, Yang et al 39 constructed 3D cloud maps of 135 typical coal particles with a 3D laser scanner, and provided a corresponding database. Therefore, combining the existing data and literature results 7 , the four-sphere filling model is selected for modeling the simulated particle shape in this paper, as shown in Fig.…”
Section: Simulation Modelingmentioning
confidence: 99%
“…Parameters associated with rock chips, such as the coarseness index ( CI ), chip size uniformity ( n ), absolute chip size ( d e ), and fractal dimension ( D ), offer valuable insights into the mechanisms and efficiency of rock breaking 10 – 12 . These parameters are instrumental in validating the rationality of simulations 13 , 14 . Therefore, the study of chip parameters is well-established in land geotechnical engineering contexts, including mining 15 , tunneling 16 , and dredging 17 processes.…”
Section: Background and Summarymentioning
confidence: 99%